2008
DOI: 10.1093/brain/awn047
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor function in frontotemporal lobar degeneration, related disorders and Alzheimer's disease

Abstract: Frontotemporal lobar degeneration (FTLD) often overlaps clinically with corticobasal syndrome (CBS) and progressive supranuclear palsy (PSP), both of which have prominent eye movement abnormalities. To investigate the ability of oculomotor performance to differentiate between FTLD, Alzheimer's disease, CBS and PSP, saccades and smooth pursuit were measured in three FTLD subtypes, including 24 individuals with frontotemporal dementia (FTD), 19 with semantic dementia (SD) and six with progressive non-fluent apha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
204
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(229 citation statements)
references
References 56 publications
22
204
1
2
Order By: Relevance
“…4, Table 1). This finding is consistent with the lack of brainstem oculomotor function impairment in MCI or AD patients with mild to moderate severity of disease (Garbutt et al 2008;Yang et al 2011Yang et al , 2013; but see Simic et al 2009).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…4, Table 1). This finding is consistent with the lack of brainstem oculomotor function impairment in MCI or AD patients with mild to moderate severity of disease (Garbutt et al 2008;Yang et al 2011Yang et al , 2013; but see Simic et al 2009).…”
Section: Discussionsupporting
confidence: 83%
“…Antisaccades (i.e., volitional saccades with opposite direction to the target) in AD exhibit impaired inhibition towards the target, as well as impaired correction of errors, with the extent of the deficiencies being related to the severity of the disease (Hershey et al 1983;Fletcher and Sharpe 1986;Moser et al 1995;Shafiq-Antonacci et al 2003;Crawford et al 2005;Garbutt et al 2008). Prosaccades (i.e., saccades directed toward the target) in AD have abnormally long latencies (Hershey et al 1983;Fletcher and Sharpe 1986;Moser et al 1995;Shafiq-Antonacci et al 2003;Crawford et al 2005;Garbutt et al 2008), but see Hershey et al (1983) and Mosimann et al (2005). Saccadic gain and speed findings in AD are controversial: some studies found impairment (Fletcher and Sharpe 1986;Hotson and Steinke 1988;Shafiq-Antonacci et al 2003) whereas others did not (Moser et al 1995;Garbutt et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a marked reduction in the ability to generate a corrective eye movement, following a saccade that was incorrectly directed towards the target. This abnormality of uncorrected errors in AD has now been replicated (Boxer et al 2006;Garbutt et al 2008;Kaufman et al 2012). Crawford et al (2005) reported that the magnitude of the errors exceeded that in healthy aging, and there was a positive correlation with the dementia severity on the mini-mental state examination (MMSE).…”
mentioning
confidence: 86%
“…The 'reverse' format requires the working memory processes of storage, inhibition and resequencing. We used the 'reverse' formats to estimate spatial and verbal working memory in common with previous clinical research ( Boxer et al 2006;Garbutt et al 2008). On the basis of previous studies, we predicted that the uncorrected errors would be strongly related to spatial working memory.…”
mentioning
confidence: 99%